PENGARUH ASSET GROWTH DAN DIVIDEN PAYOUT RATIO TERHADAP HARGA SAHAM INDUSTRI PERBANKAN PADA INDEKS SAHAM LQ-45 BURSA EFEK INDONESIA - SARI, AMILIA PARAMITA (LP2MTBM MAKARIOZ, 2023)
The study aims to determine the effect of the asset growth and dividend payout ratio on the share price, either partially or simultaneously. The study refers to the banking sub-sector that is included in the LQ-45 listed on the Indonesian Stock Exchange for the period 2018–2022. This research method is descriptive-quantitative and used for data collection using secondary data. The analytical methods used in this study are classical assumption tests, double linear regression, and hypothesis tests. From the results of the research, it can be concluded that the asset growth and dividend payout ratio simultaneously has a significant effect on the stock price. partially, only the ratio of dividend payments has a negative impact on the stock price